2020
DOI: 10.3389/fped.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Determinants of Child Maltreatment in Japan

Abstract: Background: Child maltreatment induces significant health problems, both during childhood and into adulthood. To prevent child maltreatment, it is important to detect perinatal risk factors for earlier intervention. The aim of this study was to evaluate the perinatal risk factors associated with child maltreatment during pregnancy. Methods: A case-control study was conducted to compare perinatal data from the Maternal and Child Health Handbook between the case and control groups. Cases were collected from chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Age difference between parents was calculated by subtracting maternal age from paternal age. As for subjective economic status, "difficult to manage" and "unstable" were collapsed for the analysis, since a low percentage of participants answered "unstable" (2.2%) [31]. The responses on feelings when they noticed the pregnancy of "muddled because it was unexpected", "puzzled" and "had no feeling" were collapsed to "unintended pregnancy" due to a low percentage of participants answering "muddled because it was unexpected" (6.1%), "puzzled" (0.2%) and "had no feeling" (0.2%), and these feelings were related to unintended pregnancy [32].…”
Section: Covariatesmentioning
confidence: 99%
“…Age difference between parents was calculated by subtracting maternal age from paternal age. As for subjective economic status, "difficult to manage" and "unstable" were collapsed for the analysis, since a low percentage of participants answered "unstable" (2.2%) [31]. The responses on feelings when they noticed the pregnancy of "muddled because it was unexpected", "puzzled" and "had no feeling" were collapsed to "unintended pregnancy" due to a low percentage of participants answering "muddled because it was unexpected" (6.1%), "puzzled" (0.2%) and "had no feeling" (0.2%), and these feelings were related to unintended pregnancy [32].…”
Section: Covariatesmentioning
confidence: 99%
“…It is reported that the background factors related to child maltreatment were unexpected/unplanned pregnancies, failure to receive pregnancy health checkups, failure to receive the Maternal and Child Health Handbook, and teenage pregnancies [1,2]. Other factors such as unmarried mothers, maternal mental disorder, low educational achievement, a history of childhood abuse, deprivation, and low-birth-weight children have also been reported to be associated with child maltreatment [2][3][4]. It is important to understand such social risk factors as well as medical risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, there may have been potential unadjusted confounders that were not measured in pregnancy notification forms. Pregnant women’s educational attainment, receipt of public assistance, existence of IPV, and inadequate prenatal care have been shown to be associated with child maltreatment [ 11 , 12 , 13 , 14 , 15 , 43 ] and other prenatal risk factors such as smoking and drinking alcohol during pregnancy [ 44 , 45 , 46 , 47 ]. Although significant risk factors identified in this study may merely be proxy variables for low socioeconomic status and do not have causal relationships with child maltreatment [ 13 ], they can be useful for identifying pregnant women in need of support.…”
Section: Discussionmentioning
confidence: 99%